Modification method for increasing content of calcium sulfate in semi-dry flue gas desulfurization gypsum

By modifying the electrolytic manganese leaching slag, and using electrolytic flue gas and glacial acetic acid, catalyzed the conversion of CaSO3 into CaSO4 in oxidized FGD gypsum, the problem of low CaSO4 content in semi-dry flue gas desulfurization gypsum is solved, and the resource utilization of FGD gypsum is realized.

CN119615294APending Publication Date: 2025-03-14YUNNAN ECOLOGICAL ENVIRONMENT ENG ASSESSMENT CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510036784.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The CaSO4 content in semi-dry flue gas desulfurization gypsum is low, which makes it difficult to use comprehensively and causes problems such as site occupation.

Method used

By impregnating and calcining the electrolytic manganese leaching residue, a modified catalyst is prepared, and by introducing electrolytic flue gas and adding glacial acetic acid, the conversion of CaSO3 into CaSO4 in the oxidized FGD gypsum is catalyzed to increase the CaSO4 content.

Benefits of technology

It effectively increases the CaSO4 content in FGD gypsum, reduces the CaSO3 and Ca(OH)2 content, realizes the resource utilization of FGD gypsum, and solves the problem of difficulty in comprehensive utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615294A_ABST
    Figure CN119615294A_ABST
Patent Text Reader

Abstract

The invention discloses a modification method for increasing the content of calcium sulfate in semi-dry flue gas desulfurization gypsum, and belongs to the technical field of resource utilization of flue gas desulfurization gypsum. The modification method comprises the following steps: (1) dipping and calcining the electrolytic manganese leaching residues to obtain a modified catalyst; (2) mixing the semi-dry flue gas desulfurization gypsum with water to prepare slurry; (3) introducing electrolytic flue gas into the slurry, adding glacial acetic acid and a modified catalyst at the same time until the pH value of the slurry is 6, continuously introducing air for 12 hours, and stopping introducing gas; and (4) standing and precipitating the slurry, then carrying out solid-liquid separation on the slurry to obtain a precipitate and a supernatant, and drying the precipitate to complete modification. According to the method, the semi-dry method FGD gypsum solid waste is modified through synergism of various wastes, the content of available effective components in the FGD gypsum is effectively increased in a manner of treating wastes with wastes, and a good foundation is laid for resource utilization of the FGD gypsum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource utilization of flue gas desulfurization gypsum and relates to a modification method for increasing the calcium sulfate content in semi-dry flue gas desulfurization gypsum. Background Art

[0002] The production process of electrolytic aluminum industry is cryolite-alumina molten salt electrolysis, in which the carbon anode is an important component in the electrolytic aluminum process, and the sulfur content is between 1.5% and 3%, which is brought in by the petroleum coke used as a binder during its baking process. Therefore, a large amount of SO2 will be generated during the electrolytic aluminum production process due to the anodic oxidation, with a concentration of 150mg / m 3 In order to ensure that the electrolytic flue gas meets the emission standards and reduce the amount of pollutants, thereby reducing the impact of electrolytic aluminum industrial production on the environment, the desulfurization process has become an indispensable process section in the electrolytic aluminum production process. Taking into account the cost and desulfurization efficiency and other reasons, the semi-dry process is mostly used for desulfurization in the electrolytic aluminum production process, and the desulfurized gypsum produced is semi-dry flue gas desulfurization gypsum (semi-dry FGD gypsum). Due to the reaction mechanism and characteristics of the semi-dry desulfurization process, the CaSO3 and Ca(OH)2 contents in the semi-dry FGD gypsum are high and the CaSO4 content is low. CaSO3 is unstable and will absorb water, swell or decompose under certain conditions. At the same time, Ca(OH)2 has expansive properties after hydration, which greatly restricts the comprehensive utilization of semi-dry FGD gypsum. In addition, the mass fraction of the available effective component (CaSO4) in the semi-dry FGD gypsum produced during the desulfurization process of electrolytic aluminum is only between 30-50%, which is far lower than the third-level standard of "GB / T 37785-2019 Flue Gas Desulfurization Gypsum". As a result, the semi-dry FGD gypsum produced during the desulfurization process of electrolytic aluminum is difficult to be comprehensively utilized. The large-scale storage of FGD gypsum has caused problems such as site occupation, which has become one of the difficult problems for electrolytic aluminum production units to solve. Taking Yunnan as an example, the annual output of desulfurization slag (FGD gypsum) in the electrolytic aluminum industry is about 160,000 tons.

[0003] Therefore, it is of great significance to increase the CaSO4 content in semi-dry FGD gypsum so that the FGD gypsum meets the comprehensive utilization standard and consume the FGD gypsum. It is necessary to provide a modification method for increasing the calcium sulfate content in semi-dry flue gas desulfurization gypsum to increase the CaSO4 content in semi-dry FGD gypsum. Summary of the invention

[0004] In order to overcome the problems in the background technology, the present invention impregnates and calcines electrolytic manganese leaching slag to supplement the manganese oxide content in the electrolytic manganese leaching slag, increases the surface active sites of the modified catalyst, and improves the catalytic reaction activity. The CaSO3 in the FGD gypsum is converted into CaSO4 by catalytic oxidation, and the CaSO3 content in the FGD gypsum is reduced while the CaSO4 content is increased. By introducing electrolytic flue gas, SO2 in the electrolytic flue gas reacts with Ca(OH)2 in the FGD gypsum to generate CaSO3, and CaSO3 is catalytically oxidized to generate CaSO4, thereby reducing the content in the electrolytic flue gas and the Ca(OH)2 content in the FGD gypsum, while increasing the CaSO4 content in the FGD gypsum, and using the waste heat of the electrolytic flue gas to heat the catalytic oxidation system to increase the catalytic oxidation reaction rate.

[0005] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0006] The modification method comprises the following steps:

[0007] (1) impregnating and calcining electrolytic manganese leaching residue to obtain a modified catalyst;

[0008] (2) mixing the semi-dry flue gas desulfurization gypsum with water to prepare a slurry;

[0009] (3) introducing electrolytic flue gas into the slurry obtained in step (2), and simultaneously adding glacial acetic acid and the modified catalyst obtained in step (1) until the pH of the slurry reaches 6, and then continuously introducing air for 12 hours, and then stopping the ventilation;

[0010] (4) After the ventilation is stopped in step (3), the slurry is allowed to settle, and then the slurry is subjected to solid-liquid separation to obtain a precipitate and a supernatant. The obtained precipitate is dried to complete the semi-dry flue gas desulfurization gypsum modification.

[0011] Preferably, in step (1), the electrolytic manganese leaching slag comes from insoluble impurities and residues in the acid leaching process section of the electrolytic manganese plant.

[0012] Preferably, the components of the electrolytic manganese leaching slag include, by mass fraction, 20-40% manganese dioxide, 10-25% silicate, 5-15% calcium oxide, 1-5% magnesium oxide, 1-5% iron oxide, 1-5% aluminum oxide, 10-20% sulfate, and the remainder is inevitable impurities.

[0013] Preferably, in the step (1), the electrolytic manganese leaching residue is added to a 0.5 mol / L MnSO4 solution at a solid-liquid ratio of 1 g:5 L for immersion, and then filtered after shaking for 6 hours to obtain a filter residue, which is then calcined.

[0014] Preferably, the calcination is carried out in an oxygen atmosphere, the calcination temperature is 300-500° C., and the calcination time is 1 hour.

[0015] Preferably, in step (2), the mass ratio of semi-dry flue gas desulfurization gypsum to water is 1:5-1:10.

[0016] Preferably, in step (3), the mass of glacial acetic acid added is 6% of the mass of semi-dry flue gas desulfurization gypsum.

[0017] Preferably, in step (3), the mass of the modified catalyst added is 0.2-1% of the mass of the semi-dry flue gas desulfurization gypsum.

[0018] Preferably, in step (3), the electrolytic flue gas is the flue gas that has been dedusted by a dust removal system during the electrolytic aluminum production process, and the flow rates of the electrolytic flue gas and air are both 250 ml / min.

[0019] Preferably, the temperature of the electrolytic flue gas is 80-110°C, and the SO2 concentration in the electrolytic flue gas is 500-3000 mg / m 3 .

[0020] Catalytic oxidation is an important way to achieve efficient oxidation of CaSO3 at room temperature and pressure. Mixing FGD gypsum with water to form a slurry creates a good medium for more efficient wet catalytic oxidation reactions.

[0021] In the process of catalytic oxidation reaction, the selection and preparation of catalyst is very important. 2+ As an important catalyst in the catalytic oxidation process, Mn 2+ The addition of will change the oxidation mechanism and oxidation process of CaSO3, thereby ensuring that CaSO3 maintains a higher oxidation rate level in a wider concentration and time range, prompting an increase in the terminal oxidation rate. The catalytic oxidation reaction process is as follows:

[0022] Mn 2+ +O2→Mn 3+ +O2 ·-

[0023] Mn 3+ +CaSO3→Mn 2+ +CaSO4

[0024] Mn 2+ →Mn 3+ →Mn 2+

[0025] Electrolytic manganese leaching residue is a solid waste generated during the production of electrolytic manganese. Its main component is manganese oxide, which has strong catalytic activity and plays a key role in redox reactions. In addition, the iron oxide contained in electrolytic manganese leaching residue can also serve as an auxiliary catalyst to improve the efficiency of catalytic oxidation reactions. Therefore, using electrolytic manganese leaching residue as a modified catalyst to catalyze the oxidation of CaSO3 to CaSO4 can not only increase the CaSO4 content in FGD gypsum, but also is an important way to reuse waste and realize the "waste-to-treasure" of solid waste.

[0026] Since electrolytic manganese leaching residue is a solid waste with complex composition and poor stability, the catalytic activity and stability of electrolytic manganese leaching residue can be significantly improved through impregnation and calcination processes, so that the electrolytic manganese leaching residue can fully exert its catalytic effect. The impregnation and calcination process can not only replenish the manganese oxide content in the electrolytic manganese leaching residue, increase the active sites on the catalyst surface, and help improve the activity of the catalytic reaction, but also change the surface morphology and pore structure of the electrolytic manganese leaching residue, increase the specific surface area and porosity, thereby enhancing the adsorption and reaction ability of the electrolytic manganese leaching residue to the reactants. At the same time, manganese ions can also form a stable manganese oxide layer, improve the thermal stability and chemical stability of the modified catalyst, and extend its service life.

[0027] In the catalytic oxidation reaction system, under acidic conditions, Mn 2+ The ions are more stable, which helps to catalyze the oxidation of key substances high-valent manganese (such as Mn 3+ or Mn 4+ ) formation and existence. In addition, the solubility of CaSO3 is higher under acidic conditions, thereby increasing the catalytic oxidation rate of CaSO3. The principle is as follows:

[0028]

[0029] SO3 2- (aq)+2H + (aq) → H2SO3(aq)

[0030] Therefore, in addition to reacting with Ca(OH)2 in FGD gypsum to provide CaSO3, the introduction of electrolytic flue gas can also create an acidic environment for the catalytic oxidation reaction to a certain extent. In addition, adding a certain amount of glacial acetic acid can play a catalytic role in the catalytic oxidation system and further promote the catalytic oxidation efficiency. On the one hand, the addition of glacial acetic acid plays a role in creating an acidic environment, which helps to activate the modified catalyst; on the other hand, glacial acetic acid can form a complex with manganese ions to stabilize the reaction intermediates. The manganese complex formed has a higher oxidation ability. The principle is as follows:

[0031] Mn 3+ +CH3COOH→Mn(CH3COO)3

[0032] During the semi-dry desulfurization process, as the desulfurization reaction continues to deepen, some metal oxides and sulfides will be wrapped on the surface of the desulfurizer particles, hindering the further occurrence of the desulfurization reaction. Therefore, there is a high content of unreacted desulfurization components, such as Ca(OH)2, in the semi-dry FGD gypsum. Therefore, after the electrolytic flue gas is introduced, the SO2 in the electrolytic flue gas will react with Ca(OH)2 to generate CaSO3. The reaction process is as follows:

[0033] Ca(OH)2+SO2→CaSO3+H2O

[0034] On the one hand, it has a desulfurization effect on the electrolytic flue gas and creates an acidic environment for catalytic oxidation. On the other hand, it provides more catalytic oxidation basic substances CaSO3 to increase the CaSO4 content in FGD gypsum, further increasing the amount of CaSO4. At the same time, the temperature of electrolytic flue gas is usually between 80-110℃, and the remaining heat can be used to heat the FGD gypsum slurry to increase the catalytic oxidation reaction rate.

[0035] Beneficial effects of the present invention:

[0036] 1. In the modification process of the present invention, the electrolytic manganese leaching slag and electrolytic flue gas used are both wastes or harmful substances. The secondary utilization of them can truly realize "turning waste into treasure", effectively treat waste with waste, and then coordinate the treatment of multiple wastes to achieve resource utilization.

[0037] 2. The present invention effectively improves the catalytic performance of the catalyst by impregnating and calcining the electrolytic manganese leaching residue, so that the obtained modified catalyst has higher catalytic performance, thereby improving its catalytic efficiency for FGD gypsum modification.

[0038] 3. The present invention constructs an acidic environment for the catalytic oxidation system by introducing electrolytic flue gas and adding glacial acetic acid, which helps to improve the catalytic oxidation efficiency.

[0039] 4. The present invention allows SO2 in the electrolytic flue gas to react with Ca(OH)2 in the FGD gypsum by introducing electrolytic flue gas. On the one hand, SO2 in the electrolytic flue gas is consumed to desulfurize the electrolytic flue gas. On the other hand, CaSO3 is generated to provide a basic substance for catalytic oxidation to form CaSO4 and increase the CaSO4 content in the FGD gypsum, thereby achieving the purpose of reducing the Ca(OH)2 content in the FGD gypsum.

[0040] 5. The present invention adds glacial acetic acid to form a complex with manganese ions, stabilizes the reaction intermediates, and improves the oxidation ability of the modified catalyst, making it easier to catalyze the oxidation of CaSO3.

[0041] 6. By modifying the semi-dry FGD gypsum according to the present invention, the content of components with no utilization value (CaSO3, Ca(OH)2) in the FGD gypsum can be effectively reduced, while the content of the available effective component CaSO4 in the FGD gypsum can be increased, so that the FGD gypsum can be utilized as a resource.

[0042] 7. When electrolytic flue gas and air are introduced, the FGD gypsum slurry can also be stirred by gas flow. During the reaction, there is no need to use special stirring equipment for stirring.

[0043] 8. The present invention realizes efficient multi-component catalytic oxidation by adding glacial acetic acid to construct the catalytic oxidation system, thereby realizing efficient modification of semi-dry FGD gypsum in electrolytic aluminum plants.

[0044] 9. The present invention uses the high-temperature acidic electrolytic flue gas generated in the electrolytic aluminum production process as the blowing gas, provides an oxidant and fully utilizes the temperature and acidity characteristics of the waste gas to create an acidic environment and temperature conditions for the catalytic oxidation system, while effectively consuming SO2 in the electrolytic flue gas. It is an important way to realize the resource utilization of waste gas and solid waste, provides a new idea for flue gas desulfurization, and has high practical significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a diagram showing the XRD and XRF detection analysis results of the unmodified semi-dry FGD gypsum in Example 1;

[0046] Figure 2 The XRD and XRF test results of FGD gypsum after SO2 was introduced into the FGD gypsum slurry; DETAILED DESCRIPTION

[0047] The present invention is further described in detail below in conjunction with specific embodiments.

[0048] In the examples of the present invention, chemical reagents not otherwise specified were all commercially available analytically pure for the experiments.

[0049] Example 1

[0050] First, the unmodified semi-dry FGD gypsum in this embodiment was subjected to XRD and XRF detection and analysis. The results are as follows: Figure 1 As shown, through Figure 1 The quantitative results of the composition of the unmodified semi-dry FGD gypsum in this embodiment can be obtained, as shown in Table 1.

[0051] Table 1

[0052] phase of matter Mass fraction (%) <![CDATA[Ca(OH)2]]> 29.8 <![CDATA[CaSO4·2H2O]]> 34.5 <![CDATA[CaF2]]> 3.5 <![CDATA[CaSO3·0.5H2O]]> 30.1 <![CDATA[CaSO4]]> 2.0

[0053] It can be seen from Table 1 that in the unmodified semi-dry FGD gypsum, the CaSO4·2H2O content is only 34.5%, and the CaSO4 content is only 2.0%, and the content of available effective components is at a relatively low level.

[0054] In this embodiment, semi-dry FGD gypsum is modified by the following method:

[0055] (1) Insoluble impurities and residues from the acid leaching process section of an electrolytic manganese plant are collected, and the components of the electrolytic manganese leaching residue are tested to determine that the components meet the requirements of manganese dioxide: 20-40%, silicate 10-25%, calcium oxide 5-15%, magnesium oxide 1-5%, iron oxide 1-5%, aluminum oxide 1-5%, sulfate 10-20%, and the remainder is inevitable impurities, and then the residue is used as a raw material for preparing a modified catalyst, i.e., electrolytic manganese leaching residue.

[0056] (2) The electrolytic manganese leaching residue was immersed in MnSO4 with a concentration of 0.5 mol / L at a solid-liquid ratio of 1 g:5 L, and filtered after shaking for 6 hours to obtain a filter residue. The filter residue was then placed in a calcining furnace, and the temperature was raised to 300°C in an oxygen atmosphere. After calcination for 1 hour, a modified catalyst was obtained.

[0057] (3) Weigh 180 g of semi-dry FGD gypsum from an aluminum electrolytic plant and mix it with 900 g of water to form a slurry. At this time, the pH is 9. SO2 gas with a temperature of 80°C and a volume fraction of 4% is blown into the slurry (the gas here is a simulated gas, which is a mixture of air and SO2 gas. The volume of SO2 is 4% of the total volume of the mixed gas, and the converted concentration is about 1142.8 mg / m 3 ), and at the same time, 10.8g of glacial acetic acid and 0.36g of modified catalyst were added to the slurry until the pH of the slurry was 6, and then air was continuously introduced for 12h, and then the aeration was stopped. During this process, after the simulated gas was introduced, the pH value was observed. When the pH value dropped to 8, part of the slurry was first dried, and the dried solid sample was subjected to XRD and XRF detection and analysis. The results are as follows Figure 2 As shown, through Figure 2 The quantitative components of the solid sample can be obtained, as shown in Table 2.

[0058] (4) After stopping the ventilation, the slurry was allowed to settle for 30 minutes, and then the slurry was separated into solid and liquid by filtering or the like to obtain a precipitate and a supernatant. The precipitate was placed in an oven and dried at 100°C for 2 hours to obtain a modified semi-dry FGD gypsum. The modified semi-dry FGD gypsum was subjected to XRD and XRF detection and analysis, and the results are shown in Table 3. The obtained supernatant was recovered and used to prepare a slurry with the semi-dry FGD gypsum.

[0059] Table 2

[0060] phase of matter Mass fraction % <![CDATA[CaSO4·2H2O]]> 33.2 <![CDATA[CaSO3·0.5H2O]]> 59.9 <![CDATA[SiO2]]> 2.4 <![CDATA[CaSO4]]> 4.4

[0061] Table 3

[0062]

[0063]

[0064] By comparing Table 1 and Table 2, it can be seen that after the introduction of simulated gas, the mass fraction of Ca(OH)2 has dropped from the original 29.8% to 0%, and the mass fraction of CaSO3·0.5H2O has increased from 34.5% to 59.9%. As an alkaline substance in the slurry, the reduction in the mass fraction of Ca(OH)2 is also one of the reasons why the pH value dropped from 9 to 8. By comparing Table 1 with Table 2, it is fully proved that the alkaline substance Ca(OH)2 in the slurry formed by the semi-dry FGD gypsum of the electrolytic aluminum plant can effectively absorb SO2 and increase the content of CaSO3. It also proves that the introduction of electrolytic flue gas does help the catalytic oxidation system to create an acidic environment.

[0065] By comparing Table 1 with Table 3, it can be seen that in the FGD gypsum, the mass fraction of CaSO4·2H2O is increased from 34.5% to 96.6%. At the same time, the contents of other substances in the FGD gypsum are reduced, and some substances have been completely converted to 0. This shows that the modification of FGD gypsum by the method of the present invention can effectively increase the CaSO4 content in the FGD gypsum and reduce the content of other substances, thereby achieving the purpose of fully converting CaSO3 to CaSO4 in the FGD gypsum, so that the FGD gypsum can be utilized as a resource and the stockpiled gypsum can be effectively consumed.

[0066] Example 2

[0067] In this embodiment, semi-dry FGD gypsum is modified by the following method:

[0068] (1) Insoluble impurities and residues from the acid leaching process section of an electrolytic manganese plant are collected, and the components of the electrolytic manganese leaching residue are tested to determine that the components meet the requirements of manganese dioxide: 20-40%, silicate 10-25%, calcium oxide 5-15%, magnesium oxide 1-5%, iron oxide 1-5%, aluminum oxide 1-5%, sulfate 10-20%, and the remainder is inevitable impurities, and then the residue is used as a raw material for preparing a modified catalyst, i.e., electrolytic manganese leaching residue.

[0069] (2) The electrolytic manganese leaching residue was immersed in MnSO4 with a concentration of 0.5 mol / L at a solid-liquid ratio of 1 g:5 L, and filtered after shaking for 6 hours to obtain a filter residue. The filter residue was then placed in a calcining furnace, and the temperature was raised to 500°C in an oxygen atmosphere. After calcination for 1 hour, a modified catalyst was obtained.

[0070] (3) Weigh 180 g of semi-dry FGD gypsum from an aluminum electrolytic plant, mix it with 1800 g of water and stir it to form a slurry, and blow SO2 with a temperature of 95°C and a volume fraction of 4% into the slurry. At the same time, add 10.8 g of glacial acetic acid and 1.80 g of a modified catalyst into the slurry until the pH of the slurry reaches 6. Then, continue to blow air for 12 hours and then stop aeration.

[0071] (4) After stopping the ventilation, the slurry is allowed to settle for 30 minutes, and then the slurry is separated into solid and liquid by filtering or the like to obtain a precipitate and a supernatant. The precipitate is placed in an oven and dried at 100° C. for 2 hours to obtain the modified semi-dry FGD gypsum. The obtained supernatant is recovered and used to prepare the slurry with the semi-dry FGD gypsum.

[0072] After the semi-dry FGD gypsum is modified in this embodiment, the increase degree of CaSO4 content in the FGD gypsum and the reduction degree of other substances are close to those in Example 1.

[0073] Example 3

[0074] In this embodiment, semi-dry FGD gypsum is modified by the following method:

[0075] (1) Insoluble impurities and residues from the acid leaching process section of an electrolytic manganese plant are collected, and the components of the electrolytic manganese leaching residue are tested to determine that the components meet the requirements of manganese dioxide: 20-40%, silicate 10-25%, calcium oxide 5-15%, magnesium oxide 1-5%, iron oxide 1-5%, aluminum oxide 1-5%, sulfate 10-20%, and the remainder is inevitable impurities, and then the residue is used as a raw material for preparing a modified catalyst, i.e., electrolytic manganese leaching residue.

[0076] (2) The electrolytic manganese leaching residue was immersed in MnSO4 with a concentration of 0.5 mol / L at a solid-liquid ratio of 1 g:5 L, and filtered after shaking for 6 hours to obtain a filter residue. The filter residue was then placed in a calcining furnace, and the temperature was raised to 400°C in an oxygen atmosphere. After calcination for 1 hour, a modified catalyst was obtained.

[0077] (3) Weigh 180 g of semi-dry FGD gypsum from an aluminum electrolytic plant, mix it with 1440 g of water and stir it to form a slurry, and blow SO2 with a temperature of 110°C and a volume fraction of 4% into the slurry. At the same time, add 10.8 g of glacial acetic acid and 1.08 g of a modified catalyst into the slurry until the pH of the slurry reaches 6. Then, continue to blow air for 12 hours and then stop aeration.

[0078] (4) After stopping the ventilation, the slurry is allowed to settle for 30 minutes, and then the slurry is separated into solid and liquid by filtering or the like to obtain a precipitate and a supernatant. The precipitate is placed in an oven and dried at 100° C. for 2 hours to obtain the modified semi-dry FGD gypsum. The obtained supernatant is recovered and used to prepare the slurry with the semi-dry FGD gypsum.

[0079] After the semi-dry FGD gypsum is modified in this embodiment, the increase degree of CaSO4 content in the FGD gypsum and the reduction degree of other substances are close to those in Example 1.

[0080] In summary, by modifying the semi-dry FGD gypsum through the method of the present invention, various wastes and harmful substances such as electrolytic flue gas and electrolytic manganese leaching residue can be fully reused, and the FGD gypsum can be modified for resource utilization, truly realizing the purpose of turning waste into treasure and treating waste with waste. At the same time, it can effectively realize the conversion of substances such as CaSO3 and Ca(OH)2 in FGD gypsum into CaSO4, thereby creating conditions for the resource utilization of FGD gypsum.

[0081] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A modification method for increasing the calcium sulfate content in semi-dry flue gas desulfurization gypsum, characterized in that: The modification method comprises the following steps: (1) impregnating and calcining electrolytic manganese leaching residue to obtain a modified catalyst; (2) mixing the semi-dry flue gas desulfurization gypsum with water to prepare a slurry; (3) introducing electrolytic flue gas into the slurry obtained in step (2), and simultaneously adding glacial acetic acid and the modified catalyst obtained in step (1) until the pH of the slurry reaches 6, and then continuously introducing air for 12 hours, and then stopping the ventilation; (4) After the ventilation is stopped in step (3), the slurry is allowed to settle, and then the slurry is subjected to solid-liquid separation to obtain a precipitate and a supernatant. The obtained precipitate is dried to complete the semi-dry flue gas desulfurization gypsum modification.

2. The modification method according to claim 1, characterized in that: In the step (1), the electrolytic manganese leaching slag comes from the insoluble impurities and residues in the acid leaching process section of the electrolytic manganese plant.

3. The modification method according to claim 2, characterized in that: The components of the electrolytic manganese leaching slag include, by mass fraction, 20-40% manganese dioxide, 10-25% silicate, 5-15% calcium oxide, 1-5% magnesium oxide, 1-5% iron oxide, 1-5% aluminum oxide, 10-20% sulfate, and the remainder is inevitable impurities.

4. The modification method according to claim 1, characterized in that: In the step (1), the electrolytic manganese leaching residue is added into a 0.5 mol / L MnSO4 solution at a solid-liquid ratio of 1 g:5 L for immersion, and then filtered after shaking for 6 hours to obtain a filter residue, which is then calcined.

5. The modification method according to claim 1 or 4, characterized in that: The calcination is carried out in an oxygen atmosphere, the calcination temperature is 300-500° C., and the calcination time is 1 hour.

6. The modification method according to claim 1, characterized in that: In the step (2), the mass ratio of semi-dry flue gas desulfurization gypsum to water is 1:5-1:

10.

7. The modification method according to claim 1, characterized in that: In the step (3), the mass of glacial acetic acid added is 6% of the mass of the semi-dry flue gas desulfurization gypsum.

8. The modification method according to claim 1, characterized in that: In the step (3), the mass of the modified catalyst added is 0.2-1% of the mass of the semi-dry flue gas desulfurization gypsum.

9. The modification method according to any one of claims 1, 2, 3, 4, 6, 7, and 8, characterized in that: In the step (3), the electrolytic flue gas is the flue gas that has been dedusted by a dust removal system during the electrolytic aluminum production process, and the flow rates of the electrolytic flue gas and air are both 250 ml / min.

10. The modification method according to claim 9, characterized in that: The temperature of the electrolytic flue gas is 80-110°C, and the SO2 concentration in the electrolytic flue gas is 500-3000 mg / m 3 .